MmpA, a Conserved Membrane Protein Required for Efficient Surface Transport of Trehalose Lipids in Corynebacterineae - Tamaryn J. Cashmore; Stephan Klatt; Rajini Brammananth; Arek K. Rainczuk; Paul K. Crellin; Malcolm J. McConville; Ross L. Coppel (Biomolecules, 2021)
Cell walls of bacteria of the genera Mycobacterium and Corynebacterium contain high levels of (coryno)mycolic acids. These very long chain fatty acids are synthesized on the cytoplasmic leaflet of the inner membrane (IM) prior to conjugation to the disaccharide, trehalose, and transport to the periplasm. Recent studies on Corynebacterium glutamicum have shown that acetylation of trehalose monohydroxycorynomycolate (hTMCM) promotes its transport across the inner membrane. Acetylation is mediated by the membrane acetyltransferase, TmaT, and is dependent on the presence of a putative methyltransferase, MtrP. Here, we identify a third protein that is required for the acetylation and membrane transport of hTMCM. Deletion of the C. glutamicum gene NCgl2761 (Rv0226c in Mycobacterium tuberculosis) abolished synthesis of acetylated hTMCM (AcTMCM), resulting in an accumulation of hTMCM in the inner membrane and reduced synthesis of trehalose dihydroxycorynomycolate (h2TDCM), a major outer membrane glycolipid. Complementation with the NCgl2761 gene, designated here as mmpA, restored the hTMCM:h2TDCM ratio. Comprehensive lipidomic analysis of the ΔtmaT, ΔmtrP and ΔmmpA mutants revealed strikingly similar global changes in overall membrane lipid composition. Our findings suggest that the acetylation and membrane transport of hTMCM is regulated by multiple proteins: MmpA, MtrP and TmaT, and that defects in this process lead to global, potentially compensatory changes in the composition of inner and outer membranes.